Rancang Bangun Sistem Informasi Persuratan dan Disposisi Elektronik Universitas Jambi - Sari, Gusti Purnama; Marzal, Jefri; Mauladi, Mauladi (Prodi Sistem Informasi FST Universitas Jambi, 2018)
The management of the correspondence of Jambi University is still done manually so it is considered less effective in its management where this condition tend to be slow in handling bureaucracy. In addition, the letter circulated manually is difficult to trace its existence. Documentation letters are poorly organized so the archives are not organized. From these problems, this research aims to Design and build an electronic disposition and correspondence information system that can be able to manage mailing activities. In order to become more effective and efficient. The research method used is Design and Creation with Rapid Aplication Development development model, which consists of Requirement Planning, Design and Implementation Workshop. The developed system also undergoes evaluation phase to know the quality of the Software. The result of this research is Laravel framework and referring to the development model of Rapid Application Development Development. The results of software testing obtain the value of functionality is 1 (good), reliability testing with maturity metrics reliability value obtained 100% and 99.8% (good) .The usability testing obtained 88.09% value is considered very feasible and meet usability aspects. Performance testing sub characteristic time behavior average 0.1505 seconds and 0.487 seconds both tests show that it meets the aspect of efficiency with good value.